Academic Development of Arabic Language in Assam: An Overview in Historical context (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article presents the historical aspect of Arabic language education in Assam. It scans the political situation of Assam over the ages, the changes in its borders over time, its relations with Arab countries since the pre-Islamic era, the introduction of Islam here by scholars, preachers and nobles in the Middle Ages, and the reasons for the propagation and spread of Arabic language and Islamic knowledge.Assam is a state where Arabic is taught by numerous institutions, both religious and secular, government and private. The article makes a historical study of the various levels of maktabs, madrasas and schools, as well as the colleges and universities working here for the propagation of Arabic language and literature. The article explores the reasons why Arabic language has not developed in the state in terms of speaking, communication and writing. The article concludes by discussing the role of scholars and professors practicing Arabic in Assam, as well as the role of students going to educational institutions outside Assam, who have especially reformed the curriculum and teaching methods.